Prioritas Strategi Pemasaran Berdasarkan Persepsi Konsumen Dalam Keputusan Pembelian Smartphone Xiaomi Menggunakan Metode Analytical Hierarchy Process (AHP) - Ariska Dian Novarianti; Gustian Djuanda (Journal of Business and Economics Research (JBE), 2022)
Smartphones have become one of the primary goods in almost everything we do which has an impact on the increasing needs of consumers. These conditions make many companies create smartphone products that are more up-to-date according to consumer needs. To support all the needs of consumers, many smartphone companies continue to develop their smartphone products and Xiaomi is one of the smartphone companies from China that takes part in enlivening the smartphone market. This research was conducted to find out what factors and sub-factors are the main priorities in the marketing mix strategy towards the purchase decision of Xiaomi smartphones, so that they can be used as input in the preparation of Marketing Strategies in the future. This respondent is a smartphone buyer based on the opinion that consumer perceptions are able to influence consumer decisions and produce purchases. For this reason, the priority of marketing strategy should be based on the perception of consumers who are real buyers of a product. Data processing uses the Analytical Hierarchy Process (AHP) method. The results of this study indicate that the factors in the priority elements of the marketing strategy that are the top priority for the decision to purchase Xiaomi smartphones in a row include promotions with a percentage value of 32%, prices with a percentage value of 31%, products with a percentage value of 25% and places with a value of 25%. the percentage of 12%. The product sub-factor that becomes the main priority is product quality (0.35). The sub-factor on the price that becomes the main priority is discount (0.39). The sub-factor in promotion that becomes the main priority is advertising (0.32). The subfactor for the product that becomes the main priority is the logistics channel (0.41).